Power Market Structure : Revisiting Policy Options - Vagliasindi, Maria (Washington, DC: World Bank, 2013)
The objectives of this power market structure study is to develop a taxonomy of the existing power market structures, as shown by the extent of vertical and horizontal unbundling found among restructured power systems across developing countries; to design an analytical framework for assessing the desirability of unbundling under the variety of economic conditions found among developing countries; and to propose insights for operational guidance on alternative market structures based on relevant criteria, in particular on the initial conditions of a country and its power sector. The study specifically examines whether power system size and coun¬try per capita income can be reliable indicators of initial conditions for guiding policy on power market structure. The results of the analysis carried out for this study confirm the following conclusions: (i) unbundling delivers results in terms of several performance indicators when used as an entry point to implement broader reforms, particularly introducing a sound regulatory framework, reducing the degree of concentration of the generation and distribution segments of the market by attracting additional public and private players and greater private sector participation; and (ii) there seems to be a credible empirical basis for selecting a threshold power system size and per capita income level below which unbundling of the power supply chain is not expected to be worthwhile.